Halal Regulation: Halal Self-Declare in Halal Certification - Maria Ulfa (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Article 4A Halal Product Assurance Cluster Law No. 11 of 2020 on Job Creation states